Evaluating change of surface topography as urban development in the south of Ho Chi Minh city based on analyzing remote sensing data - Van, Tran Thi; Y, Bui Thi Thy; Bao, Ha Duong Xuan (Vietnam Journal of Earth Sciences, 2015)
The low-lying swamps represent a natural shape of a region, which is the location of the ecological balance, help regulate water flow. Since unscientific urban development, especially build on low-lying areas will lead to more consequences. This paper presents the application of remote sensing to detect and assess changes in the surface topography through the transformation of low-lying areas, ponds due process of urban development for the two regions Nha Be and 7 District. Research has used Landsat images to assess the current state and to detect changes in the low-lying areas of time in 1990 and 2010. Image classification method combined band ratio helped identify surface features, especially the urban and water with classification accuracy over 80% for both the satellite image. From the current state and change maps constructed, study showed statistically urbanization rate in these two areas increased rapidly, while the disappearance of low-lying swamps was quite evident through the significant reduction of their area in 20 years. The research results are a good reference support for urban management, particularly in the fight against flooding on site as well as for the urban area of Ho Chi Minh City. Tài liệu dẫn Đặng Văn Bào, Đào Đình Bắc, Nguyễn Hiệu, Đặng Kinh Bắc, 2010: Nghiên cứu địa mạo cho quy hoạch mở rộng đô thị Hà Nội về phía tây. Tuyển tập các báo cáo khoa học, Hội thảo khoa học quốc tế Địa lý Đông Nam Á lần thứ X, Hà Nội, 23-26/11/2010; Nxb. ĐH Sư phạm, tr.132-139 Phạm Văn Cự, 1996: Xây dựng bản đồ địa mạo một vùng đồng bằng trên cơ sở phối hợp hệ xử lý ảnh số và hệ thông tin địa lý, Luận án Tiến sỹ, Thư viện Quốc gia, Hà Nội, 140tr. Trần Quốc Cường, 2004, Ứng dụng Hệ thông tin địa lý và ảnh viễn thám vào việc đánh giá tác động của việc khai thác than lộ thiên tới địa hình và đường bờ biển Cẩm Phả - Cửa Ông, Tạp chí Địa chất, số 283. Nguyễn Đỗ Dũng. Giải quyết vấn nạn ngập lụt: Thêm không gian cho nước, 2009, http://dothivietnam.org/2009/05/01/them-khong-gian-cho-n%C6%B0%E1%BB%9Bc/ Nguyễn Đỗ Dũng. Ngập lụt Tp. HCM: đi tìm căn nguyên, 2011, http://dothivietnam.org/2011/02/28/ngapluthcmc/. Châu Quỳnh, Nald Eckert, Moritz Maikamper, Barbara Horst, Frank Shcwartze, 2013: Cẩm nang Quy hoạch và Thiết kế Đô thị Thích ứng với Biến đổi khí hậu cho Tp. HCM/Việt Nam. Trường ĐH Kỹ Thuật Brandenburg Cottbus. 65-68. Lê Văn Trung, 2015: Giáo trình viễn thám. Nxb. Đại học Quốc gia Tp. HCM. Trần Thị Vân, Hoàng Thái Lan, Lê Văn Trung, 2011: Nghiên cứu thay đổi nhiệt độ bề mặt đô thị dưới tác động của quá trình đô thị hóa ở thành phố Hồ Chí Minh bằng phương pháp viễn thám, Tạp chí Các khoa học về Trái đất, Nxb Khoa học TN&CN thuộc Viện KH&CN Việt Nam, tập 33, số 3, pp. 347-359 Trần Thị Vân, 2011: Ứng dụng viễn thám và GIS giám sát đô thị hóa thành phố Hồ Chí Minh thể hiện qua các mặt không thấm, Tạp chí Phát triển Khoa học và Công nghệ, Nxb. Đại học Quốc gia Tp. HCM, tập 14, số M1, pp. 65-76.